Penerapan Metode Field trip untuk Meningkatkan Keterampilan Menulis Cerpen Peserta Didik kelas VII SMP PKBM Darul Hikam - Malik, Ilham; Zuhdi, Rasyid (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Writing skills are one of the essential skills needed by seventh-grade students in the subject of Indonesian Language. One of the Indonesian language subjects is writing short stories. One way to improve short story writing skills is through various methods, one of which we can use is the field trip method. In this study, field visits were conducted in two cycles with four stages each, namely (1) activity planning; (2) activity implementation; (3) activity observation; and (4) activity reflection. Each seventh-grade student of PKBM Darul Hikam SMP in Kuwarasan Kebumen is a subject of the research. With the help of the Indonesian language teacher, this research was conducted. Interview techniques, documentation, observation, and evaluation or tests are the data collection methods used. The action hypothesis,